Invasion Ecology Of A Tropical Fern (Pneumatopteris Afra (CHRIST.) Holttum) In Nigeria: Developing Predictive Spatial Model - Festus, Akomolafe Gbenga (Pusat Pengajian Sains Kajihayat, 2020)
The invasion of wetlands by Pneumatopteris afra in some parts of Lafia, Nigeria has posed threats to the wetlands by reducing the amount of light penetration and hindering water flow. Therefore, this study aims at building a predictive spatial model of distribution of P. afra and use functional traits approach to obtain a mechanistic understanding of the community dynamics and ecosystem properties of invaded and non-invaded wetlands. Six wetlands were chosen, consisting of three invaded and three non-invaded sites in Lafia, Nigeria. Each site has an area of 500 m x 500 m demarcated for the study. The occurrence data of P. afra at each invaded site was obtained. This data, coupled with bioclimatic variables, were used to build a maxent predictive model of distribution of P. afra in Lafia and entire Nigeria.